Visible Light-Promoted Enhanced Photocatalytic Hydrogen Generation by the CeF3:Ho3+-Incorporated TiO2 Nanosystem - Verma A.K.; Tripathi P.; Dubey A.; Vishwakarma N.K.; Sinha A.S.K.; Singh S. (My University, 2025)
Wide-spectrum solar energy harvesting is of great significance for high-band semiconductors. The present article describes the hydrogen generation from aqueous methanol over a TiO2 up-conversion (CeF3:Ho3+) nanosystem (CHT) under visible light irradiance. In situ CeF3:Ho3+ nanoparticle incorporation into TiO2 was carried out, and CeF3:Ho3+ nanoparticles (∼4 to 8 nm) were synthesized using a simple polyol reduction method using triethanolamine as a reducing agent. The XRD, UV-Vis, XPS, TEM, BET, and SEM studies reveal the successful formation of a CeF3:Ho3+-incorporated TiO2 nanosystem. The enhanced photocatalytic activity of the CeF3:Ho3+-incorporated TiO2 nanosystem (CHT) was asserted through the peak hydrogen evolution rate (79.85 μmol h-1) under visible light irradiance. Furthermore, the solar-to-hydrogen conversion efficiency (1.37%) and apparent quantum efficiency (4.00%) for the peak rate were calculated and indicated that this could be used as an effective photocatalyst system. The results obtained from wavelength-dependent photocatalytic tests demonstrate that the reaction proceeds through energy absorption from a wide-range wavelength of visible light. For the first time, the in situ incorporation of nano-sized up-conversion material CeF3:Ho3+ into TiO2 and its utility for efficient sustainable hydrogen generation under visible light irradiance were accomplished with ease. © 2023 American Chemical Society.